Redescription of Pseudoparomius linearis (Stål), and descriptions of three new species of Pseudoparomius Harrington (Rhyparochromidae: Heteroptera) - Dellapé, Pablo Matías; Coscarón, María Del Carmen (Zootaxa, 2005)
Pseudoparomius linearis Stål is redescribed and three new species: P. brailovskyi, P. slateri, and P. bimaculatus from Argentina, Bolivia, Brazil, and Uruguay, are described and illustrated.